Puppets Know Best: An Arts-Based Exploration of Scholarly Identity, Liminality and Soulful Research - Levesque, Lauren Michelle; Rozuel, Cecile (Art/Research International)

(untitled) (University of Alberta, 2022)
This article addresses the struggle of crafting a recognized professional scholarly identity, and reflects on the significance of puppets to interrupt this struggle, assert one’s voice, and creatively occupy one’s space. Our interdisciplinary contribution aims to extend conversations on the realities of academic life that are often muted or diluted such as anxiety, self-doubt, weariness and failure, with implications for creative research practices. We engage the aforementioned realities through a mix of creative and whimsical writing styles (e.g., human-puppet dialogues; poetry; reflection), leveraging insights from the Jungian psychological approach to archetypal symbol and the imagination as well as transformative arts-based approaches involving storytelling, voice, and liminal space. After exploring our own experiences carving out space as creative and reflective scholar-practitioners, we discuss two examples where puppets disrupted the status quo of particular academic settings and provided opportunities for different, more spontaneous forms of engagement with the self and with others.